2016
DOI: 10.1037/cdp0000072
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ characteristics as predictors of adolescents’ ethnic–racial identity: An examination of Mexican-origin teen mothers.

Abstract: The current longitudinal study examined Mexican-origin mothers’ cultural characteristics and ethnic socialization efforts as predictors of their adolescent daughters’ ethnic-racial identity (ERI) exploration, resolution, and affirmation. Participants were 193 Mexican-origin adolescent mothers (M age = 16.78 years; SD = .98) and their mothers (M age = 41.24 years; SD = 7.11). Findings indicated that mothers’ familism values and ERI exploration were positively associated with mother-reported ethnic socialization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…Hughes and colleagues (2016) further delineated that, to understand parents’ teaching about race and ethnicity, researchers need to investigate the links between discrimination, identity, and socialization experiences in concert and in response to context to fully describe how families help foster ethnic minority youth adaptation. We propose that maternal cultural value endorsement and identity factors drive maternal socialization messages (Derlan, Umaña-Taylor, Updegraff, & Jahromi, 2016; Knight, Carlo, Mahrer, & Davis, 2016), and that contextual experiences of discrimination are key to messages about discrimination (Hughes et al, 2016). At the same time, as youth hear these messages, they influence their own endorsement of values, identity, and perceptions of discrimination (Derlan et al, 2016; Hughes et al, 2016; Knight et al, 2016).…”
Section: Ethnic–racial Socializationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hughes and colleagues (2016) further delineated that, to understand parents’ teaching about race and ethnicity, researchers need to investigate the links between discrimination, identity, and socialization experiences in concert and in response to context to fully describe how families help foster ethnic minority youth adaptation. We propose that maternal cultural value endorsement and identity factors drive maternal socialization messages (Derlan, Umaña-Taylor, Updegraff, & Jahromi, 2016; Knight, Carlo, Mahrer, & Davis, 2016), and that contextual experiences of discrimination are key to messages about discrimination (Hughes et al, 2016). At the same time, as youth hear these messages, they influence their own endorsement of values, identity, and perceptions of discrimination (Derlan et al, 2016; Hughes et al, 2016; Knight et al, 2016).…”
Section: Ethnic–racial Socializationmentioning
confidence: 99%
“…We propose that maternal cultural value endorsement and identity factors drive maternal socialization messages (Derlan, Umaña-Taylor, Updegraff, & Jahromi, 2016; Knight, Carlo, Mahrer, & Davis, 2016), and that contextual experiences of discrimination are key to messages about discrimination (Hughes et al, 2016). At the same time, as youth hear these messages, they influence their own endorsement of values, identity, and perceptions of discrimination (Derlan et al, 2016; Hughes et al, 2016; Knight et al, 2016). In this study, we attempted to address this complexity by integrating these key variables across multiple reporters while also introducing and examining the role of a fourth type of cultural socialization, familism socialization, or teaching youth values about the centrality and importance of family, that we believe is key to understanding socialization practices in Latino families.…”
Section: Ethnic–racial Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a 2-year longitudinal study of 749 Mexican American fifth-graders and their families, Umana-Taylor and colleagues (2014) found that mothers’ ERS messages at Wave 1 predicted youth’s identity exploration and resolution 2 years later. More recent scholarship also suggests that mothers’ ERS messages mediate the relation between mothers’ and youth’s ERI (Derlan, Umaña-Taylor, Updegraff, & Jahromi, 2016, 2017). This means that parents’ identity beliefs affect the socialization messages they give and these messages, in turn, influence youth’s ERI.…”
Section: Multidimensional Model Of Acculturationmentioning
confidence: 99%
“… Umaña-Taylor and Fine (2004) compiled the Ethnic Identity Scale (EIS) for 17 items on the basis of MEIM-R. In 2015, it simplified the scale to nine questions ( Derlan et al, 2015 ). Parham and Helms (1981) compiled the Racial Identity Attitudes Scale-Black (RIAS-B), after which Cross and Vandiver (2001) compiled the Cross Racial Identity Scale (CRIS).…”
Section: Introductionmentioning
confidence: 99%